Simulation Verification of the Three-phase Single Input/Output PWM Rectifier Model and its Controller Design - CHEN Tao; ZHANG Zhixue; MEI Wenqing (Kongzhi Yu Xinxi Jishu)
The digital model of three-phase PWM rectifier is always the hot topic of research. This thesis testifies the three-phase single input/output (SISO) PWM rectifier model, based on which the controller is designed and its control effect is demonstrated, the simulation results and conclusions are consequently provided.